RBC Haemolysis Prevention and Antioxidant Activity of Barleria prionitis - Hemant A. Sawarkar (Science Faculty of Chiang Mai University, 2019)
Rural people across various regions of India uses leaf juice as well as they chew leaves of Barleria prionitis in treatment of oral ailments. Some studies pointed involvement of free radicals in oral ailments like aphthous ulcers. In this study the total phenolics and flavanoids were quantified in the extracts. The free radical scavenging activity was evaluated using in-vitro antioxidant assays, along with RBC haemolysis prevention activity. Results of FTC and TBA method suggested higher antioxidant potential of ethanolic extract than aqueous extract, thus further evaluation was carried out on ethanolic extract. Results of antioxidant activity and erythrocyte haemolysis prevention assay suggested significant potency (P value< 0.05) for ethanolic extract of the herb as compared to vitamin C. IC50 values for EBP and vitamin C were calculated by linear regression and found to be 622.90 mg/ml and 309.65 mg/ml (H2O2 radical scavenging), 505.98 mg/ml and 263.67 mg/ml (DPPH radical scavenging) and 646.93 mg/ml and 333.56 mg/ml (RBC haemolysis prevention). Based on findings of this study, we conclude the usefulness of Barleria prionitis in treatment of oral ailments may be due to its antioxidant potential.